Extracts from Glioma Tissues following Cryoablation Have Proapoptosis, Antiproliferation, and Anti-Invasion Effects on Glioma Cells. (10th April 2014) - Liu, Tianzhu; Wang, Xin; Yin, Zhilin; Pan, Jun; Guo, Hongbo; Zhang, Shizhong
Abstract : Objective . This study is to investigate the in vivo apoptotic processes in glioma tissues following cryoablation and the effects of glioma tissue extracts on GL261 glioma cells in vitro . Methods . TUNEL and flow cytometry analysis were performed to detect the apoptotic processes in the glioma tissues following cryoablation and in the GL261 cells treated with cryoablated tumor extracts. The scratch assay, the transwell assay, and Western blot analysis were carried out to evaluate the effects of cryoablated tumor extracts on the migration, invasion, and proliferation of tumor cells. Results . Our in vivo results indicated that the rapid-onset apoptosis was induced via the intrinsic pathway and the delayed apoptosis was triggered through the extrinsic pathway. The in vitro results showed that extracts from glioma tissues following cryoablation induced apoptosis via extrinsic pathways in GL261 glioma cells. Furthermore, cryoablated tumor extracts significantly inhibited the migration and proliferation of these cells, which would be related to the inhibition of ERK1/2 pathway and the activation of P38 pathway. Conclusion . Glioma cells surviving in cryoablation undergo intrinsic or extrinsic apoptosis. Augmenting the induction of apoptosis or enhancing the cryosensitization of tumor cells by coupling cryoablation with specific chemotherapy effectively increases the efficiency of this therapeutic treatment.